Village stay reservation and management system for tourism industry in Malaysia / Abidah Mat Taib ... [et al.] - Mat Taib, Abidah; Zainuddin, Nur Athirah; Haron, Noorazalia Izha; Mohd Zukri, Nurul Hidayah (UiTM Cawangan Perlis, 2020)
Tourism industry in Malaysia is being developed to be better thus, making Malaysia as one of the most attractive countries to visit. Many Village Stays in Malaysia are owned and managed by inexperienced personnel and have inefficient system. This makes local products and nearby tourist attractions not able to be advertised properly or are not made known to the public. So, the objectives of this project are to develop Village Stay Reservation and Management System that caters for the information of the local tourist attraction products and to evaluate Village Stay Reservation and Management System in terms of perceived ease of use. In order to achieve the objectives, this project develops the system using PHP programming language and tests the system of its functionality, usability and user acceptance. There are fifteen respondents who tested the system. A set of questionnaires was used to collect the data. The mean for user acceptance test is 3.77 while for user reaction in usability testing is 3.74. The respondents are satisfied with the system in terms of its functionality. In conclusion, this research has achieved the objectives. It is shown that the users can deal more effectively and efficiently when using this system. This system will reduce the workload of staffs when using an online system to monitor the reservation as well as attending to other chores.